1998
DOI: 10.1103/physrevlett.81.3960
|View full text |Cite
|
Sign up to set email alerts
|

Pd/Cu Site Interchange and Non-Fermi-Liquid Behavior inUCu4Pd

Abstract: to be published in Phys. Rev. Lett., LA-UR-98-3125) X-ray-absorption fine-structure measurements of the local structure in UCu4Pd are described which indicate a probable lattice-disorder origin for non-Fermi-liquid behavior in this material. Short Pd-Cu distances are observed, consistent with 24 ± 3% of the Pd atoms occupying nominally Cu sites. A "Kondo disorder" model, based on the effect on the local Kondo temperature TK of this interchange and some additional bond-length disorder, agrees quantitatively wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 12 publications
7
43
0
Order By: Relevance
“…The Ce-Rh/Ru fits indicate Θ cD =250 (20) The last example we present here is that of UCu 4 Pd. These results have been published previously [20][21][22]. To summarize, although the system was originally thought to be well ordered, a significant fraction (order of 25%) of the Pd atoms were found to reside on the nominally Cu sites.…”
Section: Disordered Non-fermi Liquids: Cerhrusi 2 and Ucu 4 Pdsupporting
confidence: 82%
“…The Ce-Rh/Ru fits indicate Θ cD =250 (20) The last example we present here is that of UCu 4 Pd. These results have been published previously [20][21][22]. To summarize, although the system was originally thought to be well ordered, a significant fraction (order of 25%) of the Pd atoms were found to reside on the nominally Cu sites.…”
Section: Disordered Non-fermi Liquids: Cerhrusi 2 and Ucu 4 Pdsupporting
confidence: 82%
“…The effect on the dynamic susceptibility will be that of an enhanced inhomogeneity rounding, which can explain the finite values of the correlation length and correlation time. It has also been shown [18][19][20] that such Kondo disorder can lead to the logarithmic temperature dependence of the specific heat coefficient and susceptibility and to a linear temperature dependence for the resistivity, as we observe in our sample for 2 T 10 K. In Montfrooij's view [16], the emergence of ordered magnetism must be understood in the context of percolation theory. In the simplest version of this idea, there will be two cerium environments.…”
supporting
confidence: 74%
“…In UCu 4 Pd µSR relaxation [4,5] and inelastic neutron scattering [8,9] values of the scaling exponent γ are found to agree (γ ≈ 0.3), indicating a remarkable scaling of the spin dynamics scale over three orders of magnitude in frequency. EXAFS studies of UCu 4 Pd [10] showed that Cu-Pd site exchange was responsible for much of the observed disorder. Subsequently, thermodynamic and especially transport properties of UCu 4 Pd were found to depend strongly on annealing [11], which EXAFS measurements [12] showed decreased the degree of site-exchange disorder.…”
Section: Introductionmentioning
confidence: 99%